2014
DOI: 10.1007/s11084-014-9355-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid RNA Exchange in Aqueous Two-Phase System and Coacervate Droplets

Abstract: Compartmentalization in a prebiotic setting is an important aspect of early cell formation and is crucial for the development of an artificial protocell system that effectively couples genotype and phenotype. Aqueous two-phase systems (ATPSs) and complex coacervates are phase separation phenomena that lead to the selective partitioning of biomolecules and have recently been proposed as membrane-free protocell models. We show in this study through fluorescence recovery after photobleaching (FRAP) microscopy tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 47 publications
0
131
1
2
Order By: Relevance
“…When the two emulsions are initially connected, DNA (blue, top panels) becomes concentrated almost immediately into the liposome-coated dextran-rich droplets on the right-hand side (red, lower panels), where mixing of the continuous phases occurs and DNA is accessible in the region immediately around individual droplets. At the first time point (o30 s), droplets on the edge of the sample already contained substantial concentrations of the fluorescently labelled DNA, consistent with rapid nucleic acid diffusion in PEG/dextran ATPS 47 and suggesting that the liposome layer posed essentially no barrier to entry. Migration of the DNA across the field of droplets, however, was much slower; note the absence of DNA fluorescence (blue, top panels) on the left-hand side even after 30 min.…”
Section: Resultsmentioning
confidence: 69%
“…When the two emulsions are initially connected, DNA (blue, top panels) becomes concentrated almost immediately into the liposome-coated dextran-rich droplets on the right-hand side (red, lower panels), where mixing of the continuous phases occurs and DNA is accessible in the region immediately around individual droplets. At the first time point (o30 s), droplets on the edge of the sample already contained substantial concentrations of the fluorescently labelled DNA, consistent with rapid nucleic acid diffusion in PEG/dextran ATPS 47 and suggesting that the liposome layer posed essentially no barrier to entry. Migration of the DNA across the field of droplets, however, was much slower; note the absence of DNA fluorescence (blue, top panels) on the left-hand side even after 30 min.…”
Section: Resultsmentioning
confidence: 69%
“…However, these studies are interesting in the context of naturally occurring liquid granules observed in cells, where the phase separation is commonly associated with interactions between RNA and intrinsically disordered proteins (IDPs) that lack any stable secondary structure. Thus, an open question in the field of polypeptide‐based coacervation is how the role of chemical sequence affects the ability of a particular system to undergo coacervation as well as the resultant material properties …”
Section: Molecular Designmentioning
confidence: 99%
“…Historically, one particularly contentious topic surrounding complex coacervation was the potential for these phase-separated compartments to serve as a type of protocell that could form the basis for the evolution of life. 7,30,[238][239][240][241][242][243][244][245] This hypothesis, originally put forth by Oparin,156,240,[245][246][247][248] has reemerged in the scientific literature though there are contentious discussions about the functional practicality of such membraneless compartments, 88,91,95,249 particularly with respect to their ability to sequester materials such as RNA without exchange. However, such systems do allow for the formation of model protocell environments that allow for the testing of specific aspects of biogenesis.…”
Section: Protocells and Membraneless Organellesmentioning
confidence: 99%
See 1 more Smart Citation
“…[19,21,52] Small biomolecules have also been used as scaffold solutes to assemble membrane-free droplets. Rapid exchange of RNA oligomers, for instance, was reported in aP EG/dextranA TPS and in polylysine/ATP coacervate droplets, [59] yet very little exchange of single-stranded (ss) DNA oligomers was observed for up to 48 hi nabinary poly(diallyldimethylammonium bromide) (PDDA)/ATP coacervate droplet population produced by microfluidics. [21] Oligo-and polynucleotides also partition unevenly in LLPSbased droplets.…”
Section: Bridging the Gap With Living Cells:i Ntracellular Biomoleculmentioning
confidence: 99%